INOVASI TEKNOLOGI DALAM DUNIA BISNIS MODERN - Bayu Wega Parahita (PUTRA JAWA PUBLISHER, 2024)
Over the past decade, e-commerce, or electronic commerce, has experienced rapid growth. Thanks to advancements in information and communication technology, e-commerce has played a vital role in transforming how businesses operate. In this article, we delve into the concept of e-commerce, its benefits, and its impact on the global economy. The evolution of information technology has completely changed the way we do business, communicate, and collaborate. In this piece, we explore the influence of information technology on the progress of modern businesses. We examine various technologies such as the internet, cloud computing, big data, and artificial intelligence. Additionally, we investigate how information technology affects different aspects of business, including marketing, management, finance, and human resources. Moreover, we address the challenges and risks associated with the use of information technology and provide suggestions for companies to overcome these obstacles. Ultimately, we emphasize that information technology will continue to be a crucial factor in the development of modern businesses. Organizations that can effectively integrate information technology will lead the way in an increasingly competitive global market.